An efficient numerical integration algorithm for the single mode compressible leonov model - Mirkhalaf, Mohsen (2011)
In this contribution, an algorithm for numerical integration of the Leonov elasto-viscoplastic model is proposed. The operator split methodology and the Newton-Raphson method are used to derive the state update algorithm and obtain the numerical solution of the discretized evolution equations. Particular effort is devoted to the reduction of the number of required residual equations in order to have a more efficient numerical implementation. The consistent tangent module is expressed in a closed form as a result of the exact linearization of the discretized evolution equations. The performance of the algorithm is validated through comparison with existing experimental data.